Comparison of two tungsten–helium interatomic potentials. Issue 9 (28th January 2015) - Wang, Li-Fang; Shu, Xiaolin; Lu, Guang-Hong
Abstract: Abstract : We have clarified the performance of two tungsten–helium analytical interatomic potentials, one of which, developed by Li et al., is a bond-order potential, and another, developed by Juslin et al., is a combination of embedded atom method potential and pair potential. Using these two potentials, we have simulated and made a full comparison of formation energy and migration energy of different defects including helium and vacancy, binding energies of helium and vacancy with helium-vacancy cluster, surface energy, as well as melting point, with reference to the corresponding results from the first-principles and experiments.